PENGARUH ONLINE CUSTOMER REVIEW, KEPERCAYAAN, HARGA, DAN RISIKO YANG DIRASAKAN TERHADAP MINAT BERBELANJA ONLINE DI PLATFORM E-COMMERCE: Studi Kasus pada Masyarakat Milenial - Setiawan, Hendra; Fatmala, Indra Ayu; Julita, Yayang (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2023)
The purpose of this research is to empirically prove the effect of online customer reviews, prices, trust, and perceived risk on online buying interest on e-commerce platforms. This research was conducted in the people of Madiun City by taking a sample using a porposive sample and obtained as many as 200 respondents. This research method uses a quantitative approach using SPSS version 20. The results of this study are online customer reviews, price, trust, and perceived risk affect purchase intention and online customer reviews, trust, perceived risk simultaneously affect purchase intention.